Evaluating the profile of psychological strategies: An applied profile for assessing the perceived effectiveness of athletes` psychological strategies in sport - Dogan, U. (Case Studies in Sport and Exercise Psychology, 2021)
An alternative assessment tool called the Profile of Psychological Strategies (ProPS) was recently developed to measure athletes` perceptions of (a) which strategies they use, (b) to pursue which psychological outcomes, and (c) how effective their strategies are in pursuing those psychological outcomes. This case study explains the process of evaluating this new, flexible, and highly applied tool`s theoretical validity/coherence, reliability, and immediate utility with 101 competitive athletes. This study showed that the theoretical validity and reliability of even nonstandardized, highly applied assessment tools can be evaluated. The ProPS was found to have good preliminary levels of divergent validity and immediate utility. The ProPS was also preliminarily found to have acceptable levels of known-group, concurrent, and convergent evidence, as well as test-retest reliability. Athletes in higher resilience and/or lower concentration disruption groups tended to report higher levels of effectiveness in selected psychological strategies. This case study can be useful for sport experts, especially sport psychology practitioners, wishing to use the ProPS to measure athletes` psychological strategies and for those aiming to evaluate their own applied assessment tool.